The Nutrition Society Medical Lecture. Obesity: from molecules to man. - Jebb, SA (1999)
Obesity is now a major public health problem in both developed and developing countries. In the UK over 16% men and 17.5% women are obese, an increase of more than 100% since 1980. However, interventions to prevent and treat obesity are hampered by an inadequate understanding of the aetiology of this condition. The present paper considers the current state of knowledge regarding the causes of obesity, including some of the genetic, metabolic, behavioural and environmental factors which influence energy balance. The present paper comprises The Nutrition Society Medal Lecture and focuses in particular on the research carried out at the MRC Dunn Nutrition Centre in Cambridge. It argues that despite decades of intensive research there is relatively little evidence of genetic or metabolic defects to explain the majority of cases of human obesity. Instead we must look to behavioural and/or environmental factors which may be underpinning the current epidemic of obesity.